Assaying Antioxidant Activity of Xanthone Derivatives - N.S. Kadam, R.P. Mahashabde (International Journal of Advanced Science and Technology, 2020)
Xanthones are tricyclic dibenzopyrans with various physicochemical  and pharmacological properties. As the xanthones obtained from extraction of natural products are relatively limited in the type and substituent’s position, synthesis of  xanthones derivatives become increasingly important. The  present study deals with synthesis of different hydroxyl xanthones (1,6 dihydroxy xanthone, 1,3,8 trihydroxy xanthone,1-hydroxy-6-(3-methyl-but-2-enyloxy)-xanthen-9-one,1,8-dihydroxy-3-(3-methyl-but-2-enyloxy) xanthen-9-one and 1-hydroxy xanthione by condensation of substituted benzoic acid and polyhydric phenols like phloroglucinol in the presence of Eaton’s reagent  as a condensing agent.  Substituted xanthone possess a wide range of biological activities such as hepatoprotective, anticancer, antifungal, antimicrobial and antioxidant activities. These compounds were screened for their antioxidant activity  by two different methods  namely,  DPPH (Diphenyl picryl hydrazine) and Ferric chloride assay. All the xanthone derivative have shown good scavenging in DPPH assay as well as reduction of iron (III) in FeCl3 assay. The compound 1,3,8 trihydroxy xanthone was found to be the most active antioxidant agent. The main objective behind the synthesis and selecting these compounds  was to study their biological activities as these class of xanthone derivatives are found to be important in various field of Pharmaceutical and chemical drug industries.